Contemplating the one in two: Witnessing the divine in marriage and prayer - Youssef, Hebatallah (AUC Knowledge Fountain, 2015)
The human being is in a constant struggle to find a place, an orientation for him/herself within a world that is supposedly an abode. He/she was assigned by God to be a vicegerent (khalifa), a representative of Him on earth. This thesis aims to tackle the fulfillment of this role through human participation in the activities of sexual intercourse within the framework of marriage and prayer as particular modes of being, and as recurring physical and metaphysical activities pertinent to human existence which could allow human beings to rise to the proximity of the Divine presence. This will be accomplished through investigating; Ibn ‘Arabi’s discussion of those activities in his book Fusus al-Hikam, specifically in the chapter that carries the title “The wisdom of singularity in the word of Muhammad” where he analyzes the prophetic saying: “Three things were made beloved to me in this world of yours: women, perfume and the solace of my eye was made in prayer” , and the Quranic Verse that says: “We will show them Our signs upon the horizons and within their souls, until it’s clear that He is the Real [41:53].” Even though, a lot of scholarship has been dedicated to investigating Ibn ‘Arabi’s doctrine regarding intercourse and prayer the novelty of this pursuit is in presenting them as a complimentary duality that serves in actualizing the above mentioned verse, i.e. that intercourse would allow us to see His signs within ourselves and prayer would allow us to see His signs upon the horizon.